Formal Properties of Recursive Virtual Machine Architectures - Belpaire, Gerald; Hsu, Nai-Ting (University of Wisconsin-Madison Department of Computer Sciences, 1975)
A formal model of hardware/software architectures is developed and applied to Virtual Machine Systems. Results are derived on the sufficient conditions that a machine architecture must verify in order to support VM systems. The model deals explicitly with resource mappings (protection) and with I/O devices. Some already published results are retrieved and other ones, more general, are obtained.